KITAB-KITAB ‘ULUM AL-HADIS - Tahir, Gustia (Al-Hikmah, 2018)
The scope of ‘ulum al-hadis generally consists of two: ilmu hadis riwayat and ilmu hadis dirayah. The development of ‘ulum al-hadis, which is its writing and collection, can be divided into seven phases or periods. Within each period, there are figures as pioneers marked by the existence of book collations. Those seven phases or periods are natal period, completion period, separately book keeping period, collation of main book period, maturation and completion period, coagulation and congealing period, and the second awakening period. The first Islamic scholar collating a book of ‘ulum al-hadis is al-Ramahhurmuzy. But, before he collated the book of al-Muhaddis al-Fasil bain al-Rawy wa al-Wa’iy, there has been a discussion of ‘ulum al-hadis. This discussion was still in the form of sheets collected from the results of Islamic scholars’ discussions; or in the form of partial branch of ‘ulum al-hadis.